Bacterial Community Diversity and Screening of Growth-Affecting Bacteria From Isochrysis galbana Following Antibiotic Treatment - Cao, Jia-Yi; Kong, Zhou-Yan; Zhang, Yu-Fan; Ling, Ting; Xu, Ji-Lin; Liao, Kai; Zhou, Cheng-Xu; Yan, Xiao-Jun (Frontiers in Microbiology, 2019)
Algal cultures are generally co-cultures of algae and bacteria, especially when considering outdoor cultivation. However, the effects of associated bacteria on algal growth remain largely unexplored, particularly in the context of Isochrysis galbana. In the present study, we investigated the effects of antibiotic on the growth of I. galbana and its associated bacterial community. We found advantageous responses of I. galbana to antibiotic exposure, evidenced by the increased growth and the maximal photochemical efficiency of PSII (Fv/Fm). Since antibiotics can cause major disturbances within bacterial community, we further conducted 16S rDNA amplicon sequencing to determine the changes of bacterial community diversity following antibiotic treatment. We found that antibiotic treatment considerably and negatively affected the abundance and diversity of bacterial community, and 17 significantly decreased bacterial species in the antibiotic-treated medium, including Pseudomonas stutzeri, were identified. Further co-culture experiments revealed that P. stutzeri inhibited the growth of I. galbana, and the inhibitory activity was retained in the cell-free bacterial filtrate. These results indicated that the negative effect of bacteria was not exclusively transmitted through contact with I. galbana but could be also mediated via secretory compounds. Taken together, our findings not only fully characterized the bacterial community associated with I. galbana and how the bacterial community changed in response to antibiotic perturbations, but also provided a valuable information about the interactions between I. galbana and its associated bacteria, which might help improve the yield and quality of I. galbana during its cultivation processes.